Ultrasonographic evaluation of urinary tract in children with chronic functional constipation - Karakelleoğlu, Cahit; Orbak, Zerrin; Şen, Bahri; Hülür, İnan and Alp, Handan and Akdağ, Recep and Taşdemir, Haydar (The Turkish Journal of Pediatrics, 1997)
Urinary tract anomalies were prospectively investigated with ultrasound in 31 children with chronic functional constipation. These children were compared with 29 healthy controls without constipation both before and after treatment. Bladder residue and upper renal tract dilatation after micturition were significantly more common in the group with constipation than in the improved after-treatment and control groups.